Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Femmes, genre, féminisme - Trat, Josette (Éd. Syllepse, 2007)
"Le retour sur l'histoire du courant féministe "lutte de classes" met en évidence l'urgence à penser les rapports sociaux de sexe en les articulant aux rapports de classe et aux rapports Nord-Sud. Quels sont les apports et les limites du Queer pour penser le genre et les oppressions? Quels sont les rapports entre les mouvements féministes et les mouvements gais et lesbiens? Quels sont les effets de la mondialisation néolibérale sur l'oppression des femmes et sur leurs luttes à l'échelle mondiale? Les questions des rapports de classe et celle du racisme ont été également remises au-devant de la scène par la révolte des banlieues dont les filles semblaient toutefois singulièrement absentes. Pourtant, elles luttent contre le sexisme, ainsi que le montre le collectif Féminin-Masculin de Vitry. A l'heure où les retours en arrière sont toujours possibles, comme en atteste l'émergence d'un mouvement masculiniste, la construction d'un courant féministe se donnant pour objectif de changer radicalement la société reste nécessaire pour gagner l'égalité réelle entre hommes et femmes."
Section: 1 v. (120 p.) ; 17 cm
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; histoire et politique; intersectionnalité; militance; premier cycle; queer; rapports de classe; rapports sociaux de sexe; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques

Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (University of Chicago Press, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Section: xii, 302 pages ; 24 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences